EDUCATIONAL CHANGE AND RETHINKING DISCIPLINARITY: A CONCEPT ANALYSIS - Rosenberg, Aron; Starr, Lisa (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2020)
This article analyzes the potential for reshaping disciplinary divides by engaging with theories and movements that relate to educational change. Generating educational structures that diverge from conventional discipline-based models are a common way of attempting contemporary educational reforms. Interdisciplinary approaches are analyzed in this paper relative to theories of change in the context of secondary level education, with a focus on Québec, Canada. The purpose of this article is to understand and give meaning to the concept of interdisciplinarity within educational change and reform. This exploration proposes a conceptual map for understanding educational change efforts that aim towards rethinking disciplinarity. A model case, NEXTschool, is included to illustrate the applied relevance of the theories and ideas explored in this paper.